Escherichia coli and Sudden Infant Death Syndrome - Bettelheim, Karl A.; Goldwater, Paul N. (Frontiers in Immunology, 2015)
This review examines the association of strains of Escherichia coli with Sudden Infant Death Syndrome (SIDS) and the possible role of these bacteria play in this enigmatic condition. The review addresses evidence for E. coli in SIDS infants, potential sources of E. coli in the environment, colonisation by commensal and pathogenic strains, the variety of currently accepted pathotypes, and how these pathotypes could compromise intestinal integrity and induce inflammation. Both intestinal and extraintestinal pathotypes are compared in relation to the apparent lability in which virulence traits can be gained or lost by strains of E. coli. The way in which E. coli infections fit with current views on infant sleeping position and other SIDS risk factors is highlighted.